CIRCADIAN RHYTHM AND INDICATORS OF SYSTEMIC INFLAMMATION IN PATIENTS WITH PSORIASIS AND CONCOMITANT ALIMENTARY OBESITY - Ya.O. Yemchenko; K.Ye. Ishcheikin; I.P. Kaidashev (Проблеми екології та медицини)
Psoriasis is one of the most common dermatoses, affecting from 2% to 4% of the world's population, according to the statistics from WHO. The recent increase in the incidence of comorbid psoriasis and obesity leads to severe, atypical, disabling, and treatment-resistant forms of dermatosis, which significantly impair the quality of life of patients, reduce the efficiency and social activity of patients, thus acquiring not only a medical but also a social significance. There is a theoretical justification for a possible role of circadian rhythm disorders, manifested by changes in eating behavior, reduced sleep duration, and individual chronotype of patients in the development of obesity, chronic low-intensity inflammation, and some chronic autoimmune diseases such as psoriasis. However, this issue remains understudied and insufficiently substantiated. Therefore, the aim of our research was to identify the correlation between the circadian rhythm in terms of changes in the chronotype of human working capacity and indicators of systemic inflammation in patients with extensive psoriasis and concomitant alimentary obesity. The results of correlation analysis showed a high negative correlation between the working capacity chronotype in patients and the level of IL-33, as well as a medium negative correlation between the working capacity chronotype in patients and the level of IL-6 and CRP. Therefore, changes in the circadian rhythm to the evening type of human working capacity chronotype may increase the level of systemic inflammation in patients with extensive vulgar psoriasis and concomitant alimentary obesity. Thus, further in-depth study of the relationship between systemic inflammation and circadian rhythm changes in patients with extensive vulgar psoriasis and concomitant alimentary obesity is promising and essential for the development of scientifically substantiated principles for early prevention and timely correction of these comorbidities.